A selective screening program for the early detection of mucopolysaccharidosis: Results of the FIND project – a 2-year follow-up study. Issue 19 (May 2017) - Colón, Cristóbal; Alvarez, J. Victor; Castaño, Cristina; Gutierrez-Solana, Luís G.; Marquez, Ana M.; O'Callaghan, María; Sánchez-Valverde, Félix; Yeste, Carmen; Couce, María-Luz
Abstract : Abstract: The mucopolysaccharidoses (MPSs) are underdiagnosed but they are evaluated in few newborn screening programs, probably due to the many challenges remaining, such as the identification of late-onset phenotypes. Systematic screening at the onset of clinical symptoms could help to early identify patients who may benefit from specific treatments. The aim of this prospective study was to assess a novel selective screening program, the FIND project, targeting patients aged 0 to 16 years with clinical manifestations of MPS. The project was designed to increase awareness of these diseases among pediatricians and allow early diagnosis. From July 2014 to June 2016, glycosaminoglycan (GAG) levels normalized to creatinine levels were determined in urine-impregnated analytical paper submitted by pediatricians who had patients with clinical signs and/or symptoms compatible with MPS. When high GAG concentrations were detected, a new liquid urine sample was requested to confirm and identify the GAG present. When a specific form of MPS was suspected, enzyme activity was analyzed using blood-impregnated paper to determine MPS type (I, IIIB, IIIC, IVA, IVB, VI, or VII). Age-specific reference values for GAG were previously established using 145 urine samples from healthy children. GAG levels were normal in 147 (81.7%) of the 180 initial samples received. A liquid sample was requested for the other 33 cases (18.3%); GAG levels were normal in 13 of these and slightly elevated in 12, although the electrophoresis study showed no evidence of MPS. Elevated levels with corresponding low enzymatic activity were confirmed in 8 cases. The mean time from onset of clinical symptoms to detection of MPS was 22 months, and just 2 cases were detected at the beginning of the project were detected with 35 and 71 months of evolution of clinical symptoms. Our screening strategy for MPS had a sensitivity of 100%, a specificity of 85%, and a positive predictive value of 24%. The FIND project is a useful and cost-effective screening method for increasing awareness of MPS among pediatricians and enabling the detection of MPS at onset of clinical symptoms.